Measurement of Road Slope based on Computer Vision. Issue 3 (March 2021) - Guo, Yuanxin; Chen, Guanyu; Zhang, Jiaming
Abstract: This paper proposes a driving road slope measurement algorithm to provide a reference for adjusting the vertical angle of headlights. It uses a combination of Canny Edge Detection and Hough Transform to process images from camera to detect and fitting lanes. The angle of ramp can be calculated by Mathematical Model.